Strategi Humas PT Pelayaran Nasional Indonesia (Persero) Dalam Membuat Tabloid Sebagai Media Informasi Publik Internal - Silvina Mayasari; Chitra Angguntiara (Jurnal Komunikasi, 2018)
ABSTRACTThe tardiness of information might cause a misunderstanding in implementing information about policy of the company. Thus, there must be a media information which is an effective one that could be a bridge so that information would reach the public internal. Public Relation strategy that is offered for this matter that the company faces is to make a media information through tabloid. This tabloid would be a media information that can be used as a socializing tool of an internal public that is run by the public relation. The author used a descriptive- quantitative research that is done using an observation technique of non participant and an interview to get more detail at Pelayaran Nasional Indonesia company (Persero). The conclusion of this research at Pelayaran Nasional Indonesia company (Persero) is useful as a media information for all of the employee in their own field in that company and it is one of the public relation’s strategies that is done to avoid the misunderstanding of information for the employee.Keywords: Public Relation Strategy, Tabloid, Media Information, Internal Public.